Do young children understand relative value comparisons? - Joyce F Benenson; Henry Markovits; Bjorn Whitmore; Christophe Van; Sara Margolius; Richard W Wrangham (PLoS ONE, 2015)
Many forms of judgments, such as those used in economic games or measures of social comparison, require understanding relative value, as well as the more complex ability to make comparisons between relative values. To examine whether young children can accurately compare relative values, we presented children 4 to 7 years with simple judgments of relative value in two scenarios. Children then were asked to compare the relative values in the two scenarios. Results show that even the youngest children downgraded evaluations of a reward when another has a larger amount, indicating the ability to make relative value judgments. When asked to compare relative values however, only the oldest children were able to make these comparisons consistently. We then extended this analysis to economic game performance. Specifically, previous results using economic games suggest that younger children are more generous than older ones. We replicate this result, and then show that a simple change in procedure, based on the initial study, is sufficient to change young children's choices. Our results strongly suggest that conclusions regarding young children's pro-social motives based on relative value comparisons should be viewed cautiously.